Genetic diversity of Pongamia pinnata in Bali, Indonesia using Inter Simple Sequence Repeat markers - Ni Luh Arpiwi; I Gusti Ayu Sugi Wahyuni; I Ketut Muksin (Society for Indonesian Biodiversity, 2019)
Abstract. Arpiwi NL, Wahyuni IGAS, Muksin IK. 2019. Genetic diversity of Pongamia pinnata in Bali, Indonesia using Inter Simple Sequence Repeat markers. Biodiversitas 20: 2134-2142. Pongamia pinnata (L.) Pierre is a member of family Leguminosae that produces seed oil for biodiesel feedstock. The aim of the present study was to determine genetic diversity of pongamia trees that grow in Bali using Inter Simple Sequence Repeat (ISSR) markers. This study is important to support the breeding program for the improvement of the biodiesel producing species. Leaf samples were taken from 26 pongamia trees grown on northern and southern coastal areas of Bali. Genomic DNA was isolated from fresh leaves sample and was amplified by Polymerase Chain Reaction (PCR) using 9 ISSR primers. The banding patterns of DNA after PCR were scored and tabulated into a binary matrix. Genetic distance was generated by pairwise distance using composite maximum likelihood. A dendrogram was constructed using Unweighted Pair Group Method Arithmetic (UPGMA) method. The binary matrix was further analyzed for Nonmetric Multidimensional Scaling (NMDS) with Primer E V.6 software. DNA concentrations ranged from 98.59-100.55 ng/?L with sufficient quality for PCR. The number of alleles for 9 primers was 43, the number of the polymorphic band was 35, and the number of monomorphic bands was 8. Percentage of polymorphism ranged from 50 to 100%. Cluster analysis of 26 DNA of pongamia trees showed that the trees were grouped into two, namely group I and II. Group I consisted of two trees only, namely Uma Anyar 1 and Penarukan 1. Group II consisted of 24 pongamia trees which were divided into 3 subgroups, namely IIA, IIB, and IIC with close genetic distance. Analysis of NMDS supported cluster analysis that 23 out of 26 pongamia trees had close genetic distance, and possibly they come from a similar source. Genetic diversity of pongamia in Bali needs to be widen possibly by the introduction of new planting materials from across Indonesia or seed procurement from different sources.